Artificial Intelligence to Control the Consumption of Islamic Banking Customers - Maryadi, Maryadi; Arief, Zaenal; Nuriasari, Selvia; Rodoni, Ahmad; Amelia, Erika (EconBank: Journal of Economics and Banking, 2024)
This study aims to complete literacy about the application of artificial intelligence technology in business functions, namely in the consumption function. This research method is a literature review by analyzing books and literature from various databases related to the research theme. The data used in this study is qualitative data from literature studies obtained from books and articles through various databases such as Scopus, Web of Science, Google Scholar, and other valid online sources to obtain research-themed material during March and April 2023. The use of mobile banking continues to increase. The features available in mobile banking provide comfort and convenience in making transactions. This can lead to consumption patterns that are not in accordance with the rules set out in Islamic law. Artificial intelligence technology can be applied in various business functions including production, distribution, procurement, and so on. In the consumption function, artificial intelligence can be designed to control consumption so that it conforms to Islamic principles, for example consuming halal goods, excessive amounts, and so on. The artificial intelligence technology adopted in mobile banking services is expected to become one of the monitoring tools to encourage Islamic banking customers to always commit to consumption rules, and prevent all forms of deviation from the correct consumption path.